Metode Evaluasi Program Literasi Keuangan pada Sekolah Dasar - Christianti, Emanuella; Yoenanto, Nono Heri; Andriani, Fitri (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
The objective of this research is to map the methodologies of assessing financial education outcomes that have been employed to date in the evaluation of financial literacy programs implemented in elementary schools. The review employs the systematic scoping review procedure and is presented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Scoping Review protocol. 12 articles were identified as satisfying the research objectives and inclusion criteria among the 139 articles obtained from the Scopus, Proquest, and EBSCO Host databases. An overview was obtained regarding the implementation of financial literacy program evaluations, which encompasses knowledge, attitudes, and financial behaviors in the context of elementary school students. The results encompass the aspects being evaluated, the measurement methods, and the duration necessary to conduct the impact evaluation.